Extract Of Gelidiella Acerosa (S-Act-1) As A Capacitation Agent For In Vitro Fertilisation In Goat - Chandrasiri, Alawattage Don Nimal (1997)

(untitled)
A study was conducted to determine if goat ovaries obtained from a slaughterhouse could be used for in vitro fertilisation (lVF). Three experiments were conducted to ascertain if a substance named S-ACT-l, extracted from a marine algae, (Gelidiella acerosa), with a chemical structure similar to heparin could be used for sperm capacitation. The acrosome reaction was tested by a dual staining technique (Experiment 1 ) and the zona free hamster penetration test (Experiment 2). In vitro maturation o f goat oocytes and fertilisation were assessed by the number of zygotes cleaving beyond the 2-cell stage (Experiment 3). Freshly ejaculated semen from two fertile bucks were used for sperm capacitation using two defined media (DM-H and DM-Ca). Heparin and S-ACT-l were tested at concentrations of 10, 20, 50 and 100 ug/ml. After incubating for 15 min. at 39° C with 5 % CO2 in air under maximum humidity, samples were stained with trypan blue and Giemsa stain (dual stain). The results indicated that the sperm treated with heparin and S-ACT - 1 showed similar staining characteristics.